An Extension of Wright Function and Its Properties - Moustafa El-Shahed; Ahmed Salem (Journal of Mathematics)
The paper is devoted to the study of the function Wα,βγ,δ(z), which is an extension of the classical Wright function and Kummer confluent hypergeometric function. The properties of Wα,βγ,δ(z) including its auxiliary functions and the integral representations are proven.